1988
DOI: 10.1159/000125055
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ethanol on Growth Hormone Secretion in Adult and Prepubertal Female Rats

Abstract: Conscious mature and immature rats were administered either saline or an ethanol (ETOH)-saline solution via a permanent intragastric cannula, and plasma growth hormone (GH) levels were measured by radioimmunoassay of external jugular blood samples drawn every 10 min through an indwelling Silastic catheter. Control injections of saline into the gastric cannula did not modify plasma GH concentrations, whereas both groups of rats which were administered ETOH showed significant decreases in plasma GH concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…As expected, the mean (ϮSEM) weights of the chow-fed and liquid diet-fed control animals were very close, at 92.7 Ϯ 3.3 and 90.9 Ϯ 4.2 g, respectively. The animals that received the EtOH liquid diet were smaller at 67.9 Ϯ 2.7 g, reinforcing the well known suppressive effects of EtOH on growth hormone (Dees et al, 1988;Dees and Skelly, 1990) and insulin-like growth factor-1 (Srivastava et al, 1995).…”
Section: Animalssupporting
confidence: 58%
“…As expected, the mean (ϮSEM) weights of the chow-fed and liquid diet-fed control animals were very close, at 92.7 Ϯ 3.3 and 90.9 Ϯ 4.2 g, respectively. The animals that received the EtOH liquid diet were smaller at 67.9 Ϯ 2.7 g, reinforcing the well known suppressive effects of EtOH on growth hormone (Dees et al, 1988;Dees and Skelly, 1990) and insulin-like growth factor-1 (Srivastava et al, 1995).…”
Section: Animalssupporting
confidence: 58%
“…In adult rats ETOH has been shown to inhibit the pulsatile secre tion of both hormones following its acute administration [8,10,19], We also have found that ETOH similarly affects the pulsa tile secretion of GH in immature female rats [ 10]. Also, chronic ETOH feeding has been shown to block the LH surge induced by pregnant-mare serum gonadotropin in immature female rats [21].…”
Section: Resultsmentioning
confidence: 83%
“…We have provided additional evidence to suggest that the effects of ETOH are due to actions at the hypothalamic level, since pituitary responsiveness to GH-releasing hormone [10] and LH-releasing hormone [8] was the same in female rats which were administered either an acute injection of ETOH or saline. Further support to this hypothesis comes from a recent study in which acute ETOH administration to castrated rats resulted in a significant decline in hypophyseal portal blood levels of LH-releasing hormone, with an accompanying decrement in serum LH, but not FSH levels [6].…”
Section: Resultsmentioning
confidence: 99%
“…These changes, as well as deficits in adult reproductive function, are due to the drug's actions at both the central and peripheral level (Ching et al, 1988;Dees et al, 1988Lang et al, 1998;Sonntag and Boyd, 1988;Sosynski and Frohman, 1992;Srivastava et al, 1995;Xu et al, 1995). Centrally, EtOH can block the secretion of luteinizing hormone-releasing hormone (LHRH) and growth hormone-releasing hormone (GHRH) and, thus, alter the secretion of LH (Ching et al, 1988; and growth hormone (GH), respectively (Dees et al, 1988Sosynski et al, 1992). Peripherally, EtOH lowers insulin-like growth factor-1 (IGF-1) mRNA synthesis in the liver (Lang et al, 1998;Xu et al, 1995) and suppresses serum levels of the peptide (Sonntag et al, 1988;Sosynski et al, 1992;Srivastava et al, 1995).…”
mentioning
confidence: 99%